2021
DOI: 10.33758/mbi.v15i10.1091
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Pariwisata Berbasis Masyarakat Di Desa Wisata Mangrove Sari, Kabupaten Brebes

Abstract: Desa Wisata Mangrove Sari merupakan daya tarik wisata yang berkembang dari hasil rehabilitasi hutan mangrove di pesisir Dusun Pandansari, Desa Kaliwlingi, Kecamatan Brebes, Kabupaten Brebes. Sejak ditetapkan sebagai desa wisata pada tahun 2016 dan secara resmi dibuka pada tahun 2017, Desa Wisata Mangrove Sari menjadi salah satu daya tarik wisata favorit di Kabupaten Brebes. Sebagai salah satu daya tarik wisata, desa wisata ini menerapkan konsep pariwisata berbasis masyarakat (CBT). Penelitian ini bertujuan unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Theoretically, the Community-based Tourism Approach and Sustainable Livelihood Approach can be discussed and then adjusted to the socio-cultural, socio-economic, and socio-ecological contexts in each region of Indonesia; then, an alternative model picture that is suitable for regional tourism development can be obtained. Akbar et al (2021) showed that the implementation of contextual community-based tourism and socio-cultural, socio-economic, and socio-ecological conditions of local communities could be seen in the case of Desa Wisata Mangrove Sari's case of Brebes Regency. Desa Wisata Mangrove Sari is a growing attraction from the results of mangrove forest rehabilitation in the coastal area of Pandansari Hamlet, Kaliwlingi Village, Brebes District, and Brebes Regency.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the Community-based Tourism Approach and Sustainable Livelihood Approach can be discussed and then adjusted to the socio-cultural, socio-economic, and socio-ecological contexts in each region of Indonesia; then, an alternative model picture that is suitable for regional tourism development can be obtained. Akbar et al (2021) showed that the implementation of contextual community-based tourism and socio-cultural, socio-economic, and socio-ecological conditions of local communities could be seen in the case of Desa Wisata Mangrove Sari's case of Brebes Regency. Desa Wisata Mangrove Sari is a growing attraction from the results of mangrove forest rehabilitation in the coastal area of Pandansari Hamlet, Kaliwlingi Village, Brebes District, and Brebes Regency.…”
Section: Introductionmentioning
confidence: 99%